Implementation of Collaborative Learning Strategis in the Independent Learning Curriculum at Boarding Schools - Talabudin Umkabu; Zulihi Zulihi (Edumaspul: Jurnal Pendidikan, 2023)
Learning with the Free Learning policy at Al Muttaqin Buper Islamic Boarding School aims to enhance graduates' competencies, both in terms of hard skills and soft skills. This, of course, provides relevance to the needs of the modern era. The experimental learning program, which offers a flexible pathway, is expected to serve as a facility for students to develop their potential according to their talents and passions. This research is intended as a manifestation of the Free Learning Curriculum policy by the Minister of Education and Culture of the Republic of Indonesia. Additionally, it addresses the challenges of implementing the curriculum in the era of globalization at Al Muttaqin Buper Islamic Boarding School. The research utilizes a literature and document study approach. Data will be collected through literature sources and document studies, which will be analyzed and presented in the discussion. The analysis of this policy provides opportunities to produce students who can play a role in religion and the nation, contributing to the generation of the nation.